Service Level Agreement Mapping and Provider Selection Using Annotated Semantic Information to WS-Agreement. Issue 3 (2nd July 2016) - Htay Win, Nwe Nwe; Qu, Ming-Cheng; Cui, Gang; Rehman, Saif Ur; Wang, Xiu-Feng
Abstract: Due to the increasing number of service agreements between service providers and users and the lack of standard in agreement specifications in service computing environments, there is need for an efficient service mapping and provider selection approach that focuses on Service Level Agreement (SLA) documents. This paper proposes a novel SLA mapping and provider selection approach with annotated ontological semantic information to WS-Agreement and advanced mapping rules using semantic web rule language (SWRL) and web ontology language (OWL) ontologies. The experimental data shows that our proposed approach is superior to other proficient approaches, because it can properly exploit ontological semantic technology in service specification and matchmaking.